Willingness of dentists in the United Arab Emirates to perform restorative and surgical treatments for patients infected with hepatitis C - Suhail H Al-Amad (BMC, 2021)
Abstract Background Dentists' refusal to treat patients infected with hepatitis C (HCV) continues to raise ethical concerns, particularly in countries where HCV is prevalent. The aim of this cross-sectional study was to assess dentists' willingness to treat patients infected with HCV and the socio-demographic variables that influence their decision. Methods An online questionnaire was disseminated to dentists practicing in the United Arab Emirates (UAE) and enquired about their willingness to perform two dental treatments: restorative and surgical, to patients infected with HCV, while hypothetically being equipped with optimal personal protective equipment. Binary logistic regression test was used to assess socio-demographic factors that predict dentists' unwillingness decision. Results Two-hundred and forty-five dentists participated in this survey. Among those, 25.6 and 19.3% were unwilling to perform dental extractions and aerosol-generating restorative dental treatments for patients infected with HCV, respectively. Dentists' clinical experience was a significant predictor of their unwillingness decision, with those of shorter clinical experience expressing greater reluctance than their counterparts (OR:1.61; 95% CI: 1.02-2.54; p = 0.042). Conclusion Patients infected with HCV who need dental care could face rejection by early career dentists, particularly if that treatment is a surgical one. Fresh dental graduates should be made aware of their ethical and legal responsibilities towards patients with infectious diseases, particularly HCV.